Qana‘ah sebagai Solusi Psiko-Sosiologis terhadap FOMO: Kajian Normatif Hadis Nabi dalam Konteks Generasi Z - M Ahsani Taqwim A.J; Nasrulloh (Al-Kindi, 2026)
This study investigates the concept of qana‘ah (contentment) as a psycho sociological solution for Fear of Missing Out (FOMO) among Generation Z, utilizing a normative hadith studies approach integrated with social psychology analysis. The research focuses on how prophetic traditions emphasizing self sufficiency and gratitude can mitigate the anxiety and comparative behaviors driven by digital media exposure. Data were analyzed through thematic analysis of relevant aḥ ādīth regarding ghina an nafs (wealth of the soul) and the discouragement of social comparison. The findings indicate that FOMO, rooted in upward social comparison and compulsive use, is a key driver of cognitive distraction and spiritual imbalance. Thematic analysis reveals that qana‘ah functions as a multi layered solution: (1) Cognitive Reframing (shifting value from external assets to internal contentment), (2) Emotional Immunity (providing stable internal gratification against Dopamine driven cycles), and (3) Behavioral Regulation (strengthening inhibitory control). The study concludes that integrating the normative framework of qana‘ah serves as a robust spiritual coping mechanism, enhancing psychological resilience and restoring cognitive focus (khusyu’) essential for digital well being among Gen Z.